PERBANDINGAN KUALITAS EKSTERNAL TELUR AYAM RAS STRAIN ISA BROWN DAN LOHMANN BROWN - Fauzan Isnanda Dirgahayu; Dian Septinova; Khaira Nova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
Laying chicken is a type of extremely popular poultry developed by small farmers. Laying chicken (layer) maintained by farmers were isa brown and lohmann brown strain. The purpose of this research was to compare between external quality of eggs (weight, shape index, and index egg) of isa brown and lohmann brown strain.This research were conducted in April 2015 at Mulawarman Laying Chicken Farm, Tegalsari village, Gadingrejo sub-district, Pringsewu district. The number of eggs observed in this research was 50 egs for isa brown strain and 50 egss for lohmann brown strain taken from the enclosure that contains 100 cages. Layer used in this research were 58 weeks. Weight and index egg obtained was analyzed by t student test in level of 5% and class of weight and shape egg by descriptive qualitative test. The results show weigths and index strains isa brown and lohmann brown were not significant (P>0,05). isa brown strain were extra large class of weight and on lohmann brown were a large class. Lohmann brown Strain have the shape egg better than isa brown. (Keywords: laying chicken, external quality of eggs, isa brown strain, lohmann brown strain)